Shear wave and strain sonoelastography for the evaluation of the Achilles tendon during isometric contractions - Schneebeli, Alessandro (Insights Imaging, 2021)
OBJECTIVES: Changes in mechanical loading as well as pathology can modify the Achilles tendon mechanical properties and therefore detection of these changes is relevant for the diagnosis and management of Achilles tendinopathy. The aim of this study was to evaluate strain and shear wave sonoelastography for their ability to detect changes in the Achilles tendon mechanical properties during a series of isometric contractions. METHODS: Longitudinal sonoelastography images of the Achilles tendon were acquired from 20 healthy participants using four different ultrasound devices; two implementing strain sonoelastography technology (SE1, SE2) and two, shear wave elastography technology (SWE1, SWE2). RESULTS: SE1 measured a decreasing strain ratio (tendon become harder) during the different contraction levels from 1.51 (0.92) to 0.33 (0.16) whereas SE2 mesaured a decreasing strain ratio from 1.08 (0.76) to 0.50 (0.32). SWE1 measured decreasing tendon stiffness during contractions of increasing intensity from 33.40 (19.61) to 16.19 (2.68) whereas SWE2 revealed increasing tendon stiffness between the first two contraction levels from 428.65 (131.5) kPa to 487.9 (121.5) kPa followed by decreasing stiffness for the higher contraction levels from 459.35 (113.48) kPa to 293.5 (91.18) kPa. CONCLUSIONS: Strain elastography used with a reference material was able to detect elasticity changes between the different contraction levels whereas shear wave elastography was less able to detect changes in Achilles tendon stiffness when under load. Inconsistent results between the two technologies should be further investigated. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s13244-021-00974-y.